Asymmetric Prins Cyclizations of O-Prenylated Salicylaldehydes - Grimm, Joyce A. A.; List, Benjamin (Synthesis, 2025)
We report the asymmetric intramolecular Prins cyclization reactions of O-prenylated salicylaldehydes to 4-chromanols. Excellent efficiencies and selectivities were herein obtained using a highly fluorinated imino-imidodiphosphate (iIDP) Brønsted acid catalyst. The presented method tolerates substrates bearing both electron-donating and electron-withdrawing groups.
Keywords: Asymmetric organocatalysis; Imino-imidodiphosphate (iIDP); Prins cyclization; 4-chromanols; O-prenylated salicylaldehydes